Synthesis of Cellulose Esters through an Oxidative Esterification of Cellulose with Cinnamaldehyde in Ionic Liquid and External Bases (Universitas Negeri Semarang, 2022)
Cellulose is a polysaccharide consisting of glucose linked by -1,4 glycosidic bonds in straight chains with the formula (C6H10O5)n. Cellulose modification uses long-chain hydrocarbon substituents from essential oils which can increase the added value of cellulose and essential oils. Oxidative esterification reaction is an efficient method for modifying cellulose with unsaturated α,β aldehyde compounds, one of which is cinnamaldehyde. Ionic liquid acts as a catalyst and solvent to accelerate the oxidative esterification reaction. This research was conducted to determine the effect of cinnamaldehyde on the synthesis of cellulose esters and the addition of an external base to the synthesis of cellulose esters. The synthesis of cellulose esters was carried out through an oxidative esterification reaction of cellulose and cinnamaldehyde which was added with ionic liquid and an external base for 6 hours at 80°C. The tests include FT-IR characterization to determine whether or not a carbonyl peak is formed, Differential Thermal Analysis/Thermal Gravimetry Analysis (TGA) and Differential Scanning Calorimetry (DSC) for thermal analysis and solubility test with acetone and DMSO solvents. The results showed that there was a peak at the wave number of 1700 cm-1 namely the C=O ester group which identified the success of the cellulose ester synthesis reaction with a degree of substitution (DS) value of 2.47.